Treatment strategies for primary early‐stage sinonasal adenocarcinoma: A retrospective bi‐institutional case‐control study. Issue 5 (8th September 2015) - Turri‐Zanoni, Mario; Battaglia, Paolo; Lambertoni, Alessia; Giovannardi, Marta; Schreiber, Alberto; Volpi, Luca; Bolzoni‐Villaret, Andrea; Lombardi, Davide; Bignami, Maurizio; Magnoli, Francesca; Facco, Carla; Antognoni, Paolo; et al.
<x xml:space="preserve">Abstract</x> Objective To investigate different treatment strategies for primary early‐stage (pT1‐T2) sinonasal adenocarcinomas. Methods Retrospective case‐control study. From 2000 to 2011, 61 cases were radically resected using an endoscopic endonasal approach. Surgery as a single treatment modality was adopted for 33 patients (study group) while it was followed by postoperative radiotherapy (poRT) in 28 patients (control group). Results Median follow‐up was 61 and 67 months for the study and control group respectively. Patients were stratified according to the pT classification and no statistically significant differences were found in terms of Overall (OS) and Recurrence‐free (RFS) survival. When analyzing the high‐grade tumors (47 cases), statistically significant differences were observed between the control and study groups both in terms of OS (90.5% ± 6.5% versus 57.6% ± 15.4%, P = 0.03) and RFS (92.3% ± 7.39% versus 80.2% ± 8.88%, P = 0.05). Using multivariate analysis, OS was independently determined by poRT (Hazard Ratio = 0.16; P = 0.03) thus confirming its protective role for high‐grade adenocarcinomas. Conclusion Our preliminary results suggest that endoscopic endonasal surgery could be used as a single treatment modality for primary early‐stage low‐grade sinonasal adenocarcinoma, resected with negative margins. Surgery followed by poRT offers the best treatment strategy not only for advanced‐stage lesions but also for high‐grade adenocarcinomas, regardless of the stage of disease at presentation. J. Surg. Oncol. 2015; 112:561–567. © 2015 Wiley Periodicals, Inc.